Clinical symptoms and functional impairment in attention deficit hyperactivity disorder (ADHD) co-morbid tic disorder (TD) patients: a cluster-based investigation - Zhongliang Jiang; Hui Xu; Anyi Zhang; Liping Yu; Xianbin Wang; Wenyan Zhang; Yonghua Cui; Ying Li (BMC Psychiatry)
Abstract Background Attention deficit hyperactivity disorder (ADHD) and tic disorder (TD) are two common neurodevelopmental disorders that frequently occur in childhood, and these two disorders often coexist. Cluster analysis provides a novel perspective on the heterogeneity of these commonly observed clinical disorders. Methods We recruited patients with comorbid ADHD and TD from Beijing Children's Hospital between May 2022 and August 2023, collecting data on their symptoms and functional impairments. The number of clusters was determined using the elbow method, and K-means clustering was conducted. Fisher discriminant analysis and silhouette score were used for validation. Additionally, we assessed premonitory urge, strengths, and difficulties among groups. We also collected samples with ADHD alone and performed cluster analyses. Results The number of clusters for the ADHD comorbid TD sample was determined to be two by the elbow method. The results of the cluster analysis showed that the ADHD comorbid TD sample could be divided into the severe TD group and the severe ADHD group. The severe TD group exhibits more pronounced tic symptoms, yet their age, ADHD symptoms, and functional impairment are all significantly lower than those of the severe ADHD group. Compared to samples with ADHD alone, the distribution of age and functional impairment among individuals does not change with the addition of TD symptoms, maintaining a parallel relationship with the severity of ADHD symptoms. Conclusion Patients with co-occurring ADHD and TD can be classified into two clusters based on age, symptoms, and functional impairment. In clinical interventions for these patients, while ADHD may require more attention, it is also crucial to identify the core symptoms of the patients. The heterogeneity in clinical symptom presentations highlights the need for individualized treatment approaches.